Adaptive Evidential Fusion for Hateful Meme Classification Utilizing the Dempster–Shafer Theory - Fatimi, Soukaina; Sabbar, Wafae; Bekkhoucha, Abdelkrim (Engineering, Technology & Applied Science Research, 2026)
Younger generations now frequently communicate through memes, which combine images and text to express humor, emotions, or opinions. However, memes can become a serious problem on social media when they promote hateful, discriminatory, or offensive content. Detecting such hostile memes remains particularly challenging due to the complex interaction between visual and textual cues. In this work, we propose a simple yet effective multimodal fusion approach, named Multimodal Hateful Meme Classification via Dempster–Shafer Evidence Theory Fusion (MHM-DS), for hateful meme detection. Instead of training a large vision–language model, we perform late fusion of independent unimodal classifiers— Bidirectional Encoder Representations from Transformers (BERT) for text and Contrastive Language–Image Pretraining (CLIP) for images—by combining their probabilistic outputs using Dempster–Shafer Evidence Theory (DST) evidential reasoning. The proposed method explicitly models uncertainty and conflict between modalities through belief masses and an ignorance term. Experiments conducted on the Facebook AI Hateful Memes dataset (10,000 samples) show that the proposed DST-based fusion achieves 70.2% accuracy and a 70.8% Area Under the Receiver Operating Characteristic Curve (AUROC), outperforming standard late-fusion baselines and unimodal models, while remaining computationally efficient and interpretable. These results demonstrate that evidential fusion provides a robust and uncertainty-aware alternative to complex multimodal transformers for hateful meme classification.